Stimulasi Intensi Berwirausaha Mahasiswa Jurusan Ekonomi dan Bisnis di Kabupaten Purwakarta - Hanna Chintia; Dedeng Abdul Gani Amruloh (Sekolah Tinggi Ilmu Ekonomi Yasa Anggana Garut, 2020)
The phenomenon of the increasing number of unemployed people, especially educated unemployed, is the impact of the large number of workers transferred to the formal sector, which ultimately does not grow and develop. Students tend to prepare themselves to be workers and not create jobs with entrepreneurship. Various government efforts to reduce unemployment, among others, by encouraging students to foster interest in entrepreneurship early on. This research was conducted to determine what factors influence the interest in entrepreneurship. In this study three independent variables were taken, namely the use of social media, income expectations and creativity and interest in entrepreneurship as the dependent variable. Primary data collection uses a probability sampling technique by distributing questionnaires to 100 respondents who are students majoring in economics and business in Purwakarta, with a quantitative research model with a verification descriptive method. The data analysis method used in this study is multiple linear regression with the help of IBM SPSS 22 software. Based on the result of research and testing has been done to show that partial use of social media, income expectations and creativity has a positive and significant effect on the interest in entrepreneurship. And the overall dependent variable has a simultaneous effect on the interest in entrepreneurship with the value of F count 75.565 with a significance level of 0,000 <0,05. And the value of R Square shows a result of 0.703 which means that all the dependent variables simultaneously have an effect of 70.3%%